Come in! Supplementary Reading Material - Hunt, Roderick (China Oxford University Press, 2012)
Biff, Chip, Kipper, along with their friends and dogs, invite a house full of children over to play. The action quickly becomes chaotic$1 (Bmesses are made, and in the midst of it all, even the dogs outside are forgotten$1! =(Buntil the end!((3z(BLots of children and dogs come to play with Biff, Chip and Kipper,(3y (Band (3z(Bmany children come to play $1! = (Band they make a big mess(3y(B)s
This short, funny tale$1 (Btypical of Level 4 stories$1 (Bis designed to support early readers by blending repetition and recognizable characters to reinforce vocabulary and comprehension. Children especially enjoy reading it multiple timess